PROMOSI SECARA ONLINE UNTUK MENINGKATKAN PENJUALAN DALAM MASA PANDEMI COVID-19 PADA KERAJINAN PATUNG BUDHA DI BR. TEGALBINGIN, UBUD, KABUPATEN GIANYAR - Ni Wayan Alit Erlina Wati; Ni Kadek Darmiti (JURNAL SEWAKA BHAKTI, 2021)
Sales activity is very important for the company. Sales of products or services can be done by various methods, either directly or indirectly, such as through agents. Sales cannot be made without the contribution of traders, agents and marketing personnel. Online promotion is carried out as an alternative to increase the number of sales during the Covid-19 pandemic. Mas Ubud Village which has the potential to make wood crafts, various types of wood crafts have been produced, of course, have a very high selling value, which can support the economy of the population. One type of wood craft is the craft of Buddha statues and yogi statues which are in great demand by tourists. Made by home craftsmen, Mrs. Ni Wayan Bakti and her husband, Mr. I Wayan Sandya, who are from Br. Tegalbingin Mas, Ubud. Mrs. Ni Wayan Bakti (51 years old) has been a craftsman for 13 years, from 2008 until now. Since the pandemic, which was accompanied by restrictions on public activities, selling sculptures through agents, namely art shops, has decreased drastically. Online promotion and sales are carried out as one of the alternatives chosen to increase sales. The service is carried out by providing assistance and counseling on how to promote and sell online through the Facebook marketplace and Instagram, so that currently handicraft products can be accessed via Facebook and instagram